The relationship between Malaysia’s residential property price index and residential properties loan supply - Law, Chee-Hong; Lim, Ghee-Thean (The Indonesian Capital Market Review, 2017)
This paper examines the linkages between residential property prices and residential property loans in Malaysia from 1999 to 2015. Even though residential properties are a basic necessity, there are few studies that estimate the long-run and short-run relationships between loans and price levels in residential properties in Malaysia. The estimations are divided into two parts: the detection of long-run relationships and the estimation the long-run and short-run elasticities from an ARDL model. The results support the hypothesis that the loan supply has a positive impact on residential price levels; the robustness test and Granger causality test also support this conclusion. This suggests the importance of closely monitoring the housing loan activities of banks via monetary or macroprudential policy to control residential property prices.